Telemedicine Screening for Diabetic Retinopathy Using Digital Technology: Foreign Experience - D. A. Andreev; N. N. Kamynina (Здоровье мегаполиса, 2024)
Background. Timely detection and treatment of diabetic retinopathy (DR) could prevent the development of blindness. However, large number of patients are diagnosed at late stages when effective treatment becomes impossible. In this context, active screening for DR plays an important role. Various screening programs have been developed, including programs using digital technologies.Objective. To analyze and summarize the literature data on digitalization of DR screening.Materials and methods. The study was carried out based on the results of a search in the PubMed / Medline bibliographic database and the Google system. The used keywords were “diabetes”, “retinopathy”, “telemedicine”, “digital technologies”, “artificial intelligence” and others. Relevant publications were selected by examining the titles and abstracts of articles.Results. The study addressed the approaches to organizing the telemedicine programs of DR screening. The examples of innovative digital technologies for performing diagnostic studies as well as the characteristics of various electronic systems and devices are presented. It was noted that the DR screening could be performed in a local center with data transfer to a regional specialized diagnostic (analytical) center where telemedicine analysis is done. All diagnostic information is available to the diabetologist who prescribes and adjusts therapy. This operating principle facilitates the interaction between various specialists and thus increases the efficiency of screening.Discussion. Although the telemedicine screening for diabetic retinopathy has already been introduced in a number of countries, it is still at its early stages of development. Many modern technologies such as portable mobile devices could be adapted and used in the implementation of telemedicine programs. Deep machine learning algorithms and other artificial intelligence-based approaches demonstrate excellent results. Some systems have already received regulatory approval.Conclusions. The early diagnostics of diabetic retinopathy could be improved by integrating innovative screening technologies in a unified digital platform implemented in routine clinical practice.